Strategi Pelaksanaan Supervisi Manajerial Kepala Sekolah dalam Meningkatkan Kinerja Guru - Darlisna, Darlisna; Sariakin, Sariakin; Irfandi, Irfandi (JESS (Journal of Education on Social Science); Vol 10 No 2 (2026): Public Participation in Public ServiceDO - 10.24036/jess.v10i2.674, 2026)
This study is motivated by the critical role of principal managerial supervision in improving teacher performance, which is a key factor in the success of the learning process. However, in practice, school supervision still faces challenges such as administrative-oriented implementation, limited time, and unscheduled activities, which reduce its impact on enhancing teacher professionalism. This study aims to describe the strategies of principal managerial supervision, analyze supporting and inhibiting factors, and evaluate its contribution to teacher performance at SMP Negeri 3 Lhoknga, Aceh Besar Regency. This research uses a qualitative descriptive approach with principals and teachers as the research subjects. Data were collected through observation, in-depth interviews, and documentation. Data analysis employed an interactive model, including data reduction, data presentation, and conclusion drawing, complemented by SWOT analysis to identify internal and external factors. The results indicate that despite existing challenges, principal managerial supervision can improve teacher performance, particularly through the principal’s commitment, harmonious working relationships, and utilization of existing supervision programs. SWOT analysis places the school in Quadrant I (growth/aggressive), indicating a significant potential to optimize supervision by leveraging internal strengths and external opportunities. In conclusion, managerial supervision is effective when implemented in a planned, collaborative, and sustainable manner, maximizing the existing strengths and opportunities.